MODEL KURIKULUM HUMANISTIK : MENGEMBANGKAN POTENSI INDIVIDU ,PERASAAN ,DAN NILAI DALAM PEMBELAJARAN - Nabila (CV. ADIBA ASIHA AMIRA, 2026)
The humanistic curriculum is an educational approach that focuses on the comprehensive development of learners’ potential, including cognitive, affective, and psychomotor domains. This study aims to explore the concept, characteristics, principles, and implementation of the humanistic curriculum in learning. The method employed is a literature review based on various relevant books and scientific journals published within the last 3–5 years. The findings reveal that the humanistic curriculum enhances students’ self-awareness, empathy, responsibility, and reflective skills. In addition, it promotes a learning environment that is meaningful, engaging, and enjoyable. Therefore, the humanistic curriculum is highly applicable in modern education that emphasizes character development.